Enhancing Fine Motor Skills in Children Aged 4–5 Years through Progressive Scissor-Cutting Activities - Yuniar; Munadiyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2026)
Fine motor skills are one aspect of development that needs to be stimulated from an early age because they play a crucial role in supporting hand-eye coordination and a child’s readiness to enter the next level of education. Preliminary observations at the Assalam Islamic Early Childhood Education indicated that the fine motor skills of 4-5-year-old children were still underdeveloped, particularly in cutting activities. This study aimed to improve children’s fine motor skills through cutting activities using paper. The study employed the Classroom Action Research method based on the Kemmis and McTaggart model, which includes the stages of planning, implementation, observation, and reflection. The research subjects consisted of 14 children in Group A, aged 4–5 years, at the Assalam Islamic Early Childhood Education. The study was conducted in two cycles: Cycle I focused on introducing the use of scissors and practicing cutting basic shapes, while Cycle II focused on practicing cutting geometric shapes. Data were collected through observation, performance assessment, and documentation, and were then analyzed using descriptive quantitative and qualitative methods. The results of the study show that children’s fine motor skills improved, as indicated by a decrease in the percentage of children in the “Not Yet Developed” category from 32% to 21% and an increase in the percentage of children in the “Developing Well” category from 17% to 31%. These findings suggest that paper-cutting activities conducted in stages are effective in improving the fine motor skills of 4–5-year old children